Answer:
IS C
Explanation:
(2x+1)(2x-1)
apply different of two formula :(a+b)(a-b)=a^2-b^2
a=2x, b=1
=(2x)^2-1^2
Simplify (2x)^2- 1^2: 4x^2-1
(2x^2)-1^2
apply rule 1^a=1
1^2=1
=(2x)^2-1
(2x)^2=4x^2
apply exponent rule:(a·b)^n=a^nb^n
=2^2x^2
-----------------------------------------------------------------------------
2^2=4
=4^2
-----------------------------------------------------------------------------
4x^2-1
__________________________________________________________
(x-2)(x+3)
apply FOIL method:(a+b)(c+d)=ac+ad+bc+bd
a=x, b=-2, c=x, d=3
=xx+x·3+(-2)x+(-2)·3
apply minus-plus rules
+(-a)=-a
xx+3x-2x-2·3
add similar elements:3x-2x=x
=xx+x-2·3
apply exponent rule:a^b·a^c=a^b+c
=x^2+x-2·3
multiply the numbers:2·3=6
=x^2+x-6
distribute parenthese
=(x^2)-(x)-(-6)
apply minus-plus rule
= -x^2-x=6
4x^2-1=x^2-x+6
_________________________________________________________
4x^2-1=x^2-x+6
switch sides =-x^2-x+6=4x^2-1
add 1 to both sides -x^2-x+6+1=4x2-1+1
simplify -x^2-x+7=4x2
subtract 4x^2 from both sides
-x^2-x+7-4x^2-4x^2
simplify -5x^2-x+7=0
________________________________________________________
a=-5, b=-1, c=7 x1,2=√(-1)^2-4(-5)7
#1 x=-1(-1)+√(-1)^2-4(-5)7 ÷ 2(-5)
=-1+√141 ÷ 10
#2 x=-(-1)-√(-1)^2-4(5)7 ÷ 2(-50
=√141-1 ÷ 10
x=-1+√141 ÷10 & -1√141 ÷10 = answer C.